Ethnologia Europaea (Vol. 42-2) - Karen Körber (Ethnologia Europaea, 2012)
Special issue: Though a seemingly stable concept in ethnological work,"family" as a lived reality took and takes on innumerable formsshaped by economic pressures, mobility and attendant socialtransformations, and biotechnical interventions. The case studiesin this special issue focus on the ways in which social actors seekto concretize as well as control what family could or should be. While (bio-)technological innovation proves vital to fulfilltraditional imaginaries of a nuclear family, communicationtechnology is a key to keep transnationally situated families incontact. Still, transnational work opportunities conflict withtraditional imaginaries of the wholesome families and impactparticularly women seeking to cross both borders and establishedfamily norms. Popular genealogy as a hobby and passionuncovers evidence that counters established narratives: insteadof long-term sedentary family lineages, evidence of migrationmuddies the waters. Family metaphor, finally, serves, in one ofthe case studies, as vocabulary to materialize imaginary kinshipties among nuns. The five case studies are complemented by fourcommentaries, exploring paths along which these themes can bedeveloped further.